Simulation Analysis of Dynamic Characteristics of Halbach Array Eddy Current Damper Under Strong Impact Load (Dandao Xuebao/Journal of Ballistics, 2023)
Aiming at the problems of recoil liquid losing effectiveness and spilling of traditional artillery recoil brake, the magnetic field distribution characteristics of the linear Halbach array were analyzed by simulation, and an eddy current damper(ECD)structure based on the Halbach permanent magnet array was proposed. By introducing the recoil equation of artillery, the mathematical analysis model of the eddy current damping force of ECD was established. The dynamics finite element simulation model of ECD was established by using Comsol software. The recoil velocity, recoil resistance and recoil displacement during the recoil of the artillery were calculated. The effects of the key dimension parameters of ECD and the coaxial eccentricity error on the damping characteristics were analyzed. The simulation results show that the ECD can satisfy the recoil characteristics of the artillery under the load excitation of combining bore resultant force and the counter-recoil force.